2015
DOI: 10.1177/1088767915570312
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Course After Discharge of Mentally Disordered Homicide and Non-Homicide Offenders

Abstract: The aim of this article was to compare the characteristics and outcome of homicide and non-homicide mentally disordered patients all of whom had been hospitalised. Seventy-four patients with a homicide conviction were compared with 521 convicted of a non-homicide offense. The former group were older, were more likely to be diagnosed with schizophrenia but less likely to have suffered from childhood adversity, and had less criminality. They also had fewer convictions during the follow-up. Little distinguished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Hence, various researchers have suggested that murderers and nonmurderers may have differences in their motivations (Richetin & Richardson, 2008). For example, Clarke et al (2016) compared mentally disordered offenders who had committed homicide to mentally disordered offenders who had committed other acts of violence. They found that homicide per-petrators were less likely to have suffered childhood adversity, had less generalized criminality, and were more likely to have a diagnosis of schizophrenia.…”
Section: Typologies Of Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, various researchers have suggested that murderers and nonmurderers may have differences in their motivations (Richetin & Richardson, 2008). For example, Clarke et al (2016) compared mentally disordered offenders who had committed homicide to mentally disordered offenders who had committed other acts of violence. They found that homicide per-petrators were less likely to have suffered childhood adversity, had less generalized criminality, and were more likely to have a diagnosis of schizophrenia.…”
Section: Typologies Of Violencementioning
confidence: 99%
“…For the homicide group (our proxy for the less criminogenic group of offenders in this high-risk offender sample), we hypothesized that their criminal/violent behavior does not stem from procriminal attitudes, and hence, we did not predict any relationship between measures of past convictions and implicit attitudes to violence in this group. We acknowledge that the distinction between homicide versus nonhomicide offenders is only a crude proxy for the distinction proposed by Moffitt (1993) for the more criminogenic and life-time antisocial offenders and for the distinction outlined by Glasser (1996), but note that such a distinction that has been used in other empirical examinations of criminal motivations (Clarke et al, 2016; Gray et al, 2003; Sherretts et al, 2017).…”
Section: Typologies Of Violencementioning
confidence: 99%
“…Similarly, it cannot be determined whether any offenders in the control sample had an SV crime in their criminal history prior to 2001. For the control sample, this would be problematic based on the criteria for their inclusion; yet other research that has used matched‐case controls cannot certify that the control sample did not contain offenders with SV previous convictions that were unknown to the police (e.g., Clarke et al, ; Soothill et al, ), and thus, it is evident that this is a limitation associated with the type of data used.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on homicide offender recidivism, though limited in frequency, has offered valuable insight into the reoffending patterns of this distinct group of offenders. 1 While some studies have focused on offenders within the U.S. (Liem et al, 2014; Neuilly et al, 2011; Roberts et al, 2007), most have centered on homicide offenders in Australia and Europe (Baay et al, 2012; Broadhurst et al, 2018; Clarke et al, 2016; Eronen et al, 1996; Gottlieb & Gabrielsen, 1990; Sturup & Lindqvist, 2014; Tiihonen et al, 1995). Overall, this research indicates that the extent of recidivism among homicide offenders varies considerably from about 1% to upwards of 80%.…”
Section: Literature Reviewmentioning
confidence: 99%